La nature en privilège : de l’effet des populations citadines aisées sur les paysages et la flore du Cœur vert de la Randstad Holland - Fabien Roussel (Développement Durable et Territoires)
The vegetated spaces located around Western cities (agricultural land, wooded areas, wetlands, abandoned spaces or recreated nature), are now integrated into metropolitan policies for the management and preservation of nature and landscapes. They are also a living and leisure environment for city dwellers, especially the more affluent. Along with reflections on green gentrification, the notion of luxury effect has been proposed to designate the effects of wealthy populations on the increase of biodiversity or, on the contrary, its impoverishment, with the authors referring to a reverse luxury effect. The question must be considered not only from a quantitative point of view, but also in the qualitative dimension of biodiversity.The vast agricultural area in the heart of Randstad Holland in the Netherlands – a conurbation of nearly 7 million inhabitants in 2018 –, referred to in Dutch legislation as the Green Heart, is an archetypal example of multifunctional management of peri-urban vegetated areas that combines agricultural, recreational and ecological issues. Initially very centralizing and regulatory, the policy in favor of nature in the Netherlands has experienced since 2010 a dynamic of disengagement of the central state, in favor of actions at regional and local levels that risk increasing the logic of landscape self-interest. A biogeographic approach was undertaken here based on botanical data, landscape observations and socioeconomic indicators to discuss the effects of affluent populations on the landscapes and flora of the Green Heart. We focused on riverbanks, which are more accessible and highly attractive to urban residents.The riverside flora associated with the most favored sectors has a very anthropophilic character, suggesting an inverted luxury effect, and highlights the qualitative dimension of biodiversity. The hygrophilous flora, which meets the conditions of wetlands and therefore the challenges of preserving biodiversity, is found in the areas furthest from the conurbation, where more modest inhabitants live. The nature targeted by the wealthy residents is more a controlled landscape setting: wooded banks or offering a clear view on the river. However, a spatial convergence is occurring between nature protection measures and the presence of wealthy populations. Some ideas are suggested concerning the management of these measures by the institutions and the resulting negotiations with local actors.